Description of a new genus, a new species and a new subspecies of snout moths (Lepidoptera: Pyralidae: Phycitinae) from Eastern Europe and Central Asia - Trofimova, Tatyana; Bidzilya, Oleksiy; Budashkin, Yuriy; Karolinskiy, Eugene (Zootaxa, 2020)
Yelenka gen. nov. is established to accommodate two species initially described in the genus Nephopterix Hübner, [1825] 1816—Yelenka hastiferella (Ragonot, 1887) comb. nov. and Yelenka gengisella (Ragonot, 1893) comb. nov. Additionally, a new species Yelenka calciferella sp. nov. from Ukraine, Russia and Western Kazakhstan, and its mountain subspecies Yelenka calciferella uyghurica ssp. nov. from Eastern Kazakhstan and Mongolia are described. The new genus is placed into the subfamily Phycitinae. Yelenka gengisella (Ragonot, 1893) sp. rev. is taken out from synonymy with Myrlaea orcella (Ragonot, 1887). Yelenka gengisella and Y. hastiferella are redescribed based on type material and additional specimens. According to DNA barcode, Y. gengisella and Y. hastiferella are placed in the same BOLD BIN. However, these species exhibit pronounced morphological characters that clearly distinguish the two taxa on the species level. The lectotype is designated for Nephopteryx [sic] hastiferella Ragonot, 1887. Comparative diagnoses, a key to species, illustrations of external characters, also male and female genitalia are provided for all species.